PENGARUH USAHA BUDIDAYA SARANG BURUNG WALET TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT KAMPUNG MERANCANG DI KABUPATEN BERAU - Rifai, Ahmad (ECO-BUILD, 2026)
This study aims to analyze the influence of swiftlet nest farming on the income improvement of the community in Merancang Village, Berau Regency. The research employed a quantitative approach with a survei method involving 30 swiftlet farmers selected through total sampling. Data were collected using a structured questionnaire and analyzed through validity, reliability, and normality tests, as well as simple linear regression and t-test. The results show a strong positive relationship between swiftlet nest farming and community income improvement, with a correlation coefficient of 0.839. The regression equation obtained is Y = 7.087 + 0.969X, indicating that each one-unit increase in swiftlet nest farming contributes to a 0.969-unit increase in community income. The t-test result (t-count = 8.168 > t-table = 1.703; sig. = 0.000 < 0.05) confirms that the hypothesis is accepted. Thus, swiftlet nest farming significantly contributes to enhancing the income and economic well-being of the local community.